Hajia Sophia: a Church, a Mosque then a Museum Mutation of the Values in the Cultural Heritage Conservation (Damascus University Journal for engineering sciences, 2021)
By the announcement to recover the previous situation of one of the world monuments, Hajia Sophia museum of Christian and Islamic arts, located in historic Istanbul, listed as a world cultural site; this article tracks the modifications and changing that occurred in Hajia Sophia since its consecration as an orthodox church in 6th century AD.The article presents the modifications via a detailed table to facilitate the Chrono-analysis of the direct causes, and the realization of these modifications according to the common concepts of the cultural heritage conservation. However, the result of every changing, usually visible, could pass a message that might transform by the time.
Keywords: Ayasofya